Characterization of Multidrug-Resistant Salmonella enterica Serovar Typhimurium Isolated in Japan - Izumiya, Hidemasa (American Society for Microbiology, 2001)
A total of 221 isolates of multidrug-resistant Salmonella enterica serovar Typhimurium in Japan were characterized in the present study. The results revealed that clonal serovar Typhimurium definitive phage type 104 strains prevailed and that these strains had drug resistance patterns, integron types, and pulsed-field gel electrophoresis patterns similar to those predominant among isolates in Western countries.